Marine algal flora of Santa Maria Island, Azores - Neto, Ana I. (2021)
BACKGROUND: The algal flora of the Island of Santa Maria (eastern group of the Azores archipelago) has attracted interest of researchers on past occasions (Drouët 1866, Agardh 1870, Trelease 1897, Schmidt 1931, Ardré et al. 1974, Fralick and Hehre 1990, Neto et al. 1991, Morton and Britton 2000, Amen et al. 2005, Wallenstein and Neto 2006, Tittley et al. 2009, Wallenstein et al. 2009a, Wallenstein et al. 2010, Botelho et al. 2010, Torres et al. 2010, León-Cisneros et al. 2011, Martins et al. 2014, Micael et al. 2014, Rebelo et al. 2014, Ávila et al. 2015, Ávila et al. 2016, Machín-Sánchez et al. 2016, Uchman et al. 2016, Johnson et al. 2017, Parente et al. 2018). Nevertheless, the Island macroalgal flora is not well-known as published information reflects limited collections obtained in short-term visits by scientists. To overcome this, a thorough investigation, encompassing collections and presence data recording, was undertaken at both the littoral and sublittoral levels down to a depth of approximately 40 m, covering an area of approximately 64 km2. The resultant taxonomic records are listed in the present paper which also provides information on species ecology and occurrence around the Island, improving, thereby, the knowledge of the Azorean macroalgal flora at both local and regional scales. NEW INFORMATION: A total of 2329 specimens (including some taxa identified only to genus level) belonging to 261 taxa of macroalgae are registered, comprising 152 Rhodophyta, 43 Chlorophyta and 66 Ochrophyta (Phaeophyceae). Of these, 174 were identified to species level (102 Rhodophyta, 29 Chlorophyta and 43 Ochrophyta), encompassing 52 new records for the Island (30 Rhodophyta, 9 Chlorophyta and 13 Ochrophyta), 2 Macaronesian endemics (Laurencia viridis Gil-Rodríguez & Haroun; and Millerella tinerfensis (Seoane-Camba) S.M.Boo & J.M.Rico), 10 introduced (the Rhodophyta Acrothamnion preissii (Sonder) E.M.Wollaston, Antithamnion hubbsii E.Y.Dawson, Asparagopsis armata Harvey, Bonnemaisonia hamifera Hariot, Melanothamnus harveyi (Bailey) Díaz-Tapia & Maggs, Scinaia acuta M.J.Wynne and Symphyocladia marchantioides (Harvey) Falkenberg; the Chlorophyta Codium fragile subsp. fragile (Suringar) Hariot; and the Ochrophyta Hydroclathrus tilesii (Endlicher) Santiañez & M.J.Wynne, and Papenfussiella kuromo (Yendo) Inagaki) and 18 species of uncertain status (11 Rhodophyta, 3 Chlorophyta and 4 Ochrophyta).